Shutter glasses as a training tool in sports vision training - changes in visual perception according to frequency and duty ratio - Jendrusch, G.; Platz, A.; Sickenberger, W. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Shutter glasses seem to be a tool for training visual functions in the context of sports vision training to increase movement coordination. Several studies discussed effects and non-effects of training with shutter glasses e.g. within coincidence anticipation (Smith & Mittroff, 2012; Reichow et al., 2010), motion cognition or short-time memory (Appelbaum et al., 2011 and 2012). No investigation justifies the training settings and strobe settings yet. Based on the necessity of an adequate load dosage to allow training effects, the present study intends to assess which strobe settings lead to a significant decrease of visual/perceptual performance. Methods: 62 subjects (31m, 31f, median of age=25, median of visual acuity 1.6 (logMAR=-0.20)) took part in 13 test series to determine afferent motion perception (DTDS, Wist et al., 2000), reaction and anticipatory dynamic vision (Jendrusch & Ehrenstein, 2008), dynamic depth perception (three-rodtest according to Helmholtz) and peripheral awareness (Oculus Twinfield 2). The results with different randomized strobe rates (level 1-8) of shutter glasses (Nike Vapor Strobe) currently used in sports vision training have been compared. Results: By increasing level (lower frequency and higher duty ratio) the afferent motion perception performance for stimulus motion duration of 280 and 420 ms decreases. Depth perception declines between level 2 and 8 respectively between level 5 and 8 according to the test velocity (7 vs. 2 mm/s). Maximum visual field decreases for blue stimuli between level 2 and 8 and for red stimuli between level 2 and 5. There is a larger decrease for red stimuli. These differences are statistically significant (p<=0.05). Reaction and anticipatory dynamic vision (timing) show no significant differences. Discussion: For different visual performance skills lower frequency and higher duty ratio leads to increasing perceptual stress. No discrete levels for changes in performance were found. The combination of different requirements in sports needs an adjustment of training for each skill/sport-specific demand. However, generalized (nonspecific) training with the shutter glasses lacks effectfocused specificity.